Indivisibility Principle of Regional Financial Management In Indonesia - Ansar; Asri Lasatu; Rahmat Bakri; Muhammad Hatta Roma Tampubolon; Siti Fatimah Maddusila (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Regional budgets (APBD) have an important role in fulfilling human rights (HAM), but the integration of human rights principles in regional financial management still faces challenges. Separate budget management is contrary to efforts to fulfill human rights comprehensively. This study focuses on aspects of budget policy towards the fulfillment of human rights, especially how the principle of indivisibility as a state obligation is realized in policies and implementation of regional financial policies. This study is a normative legal study with a conceptual and legislative approach. The results of the study indicate that optimal and participatory regional financial planning ensures the fulfillment of basic rights in a comprehensive and interrelated manner, such as the right to health which includes health services, a healthy environment, and social security. The APBN and APBD reflect the sovereignty of the state and the aspirations of the people, with the main goal of achieving community welfare. Budget management must prioritize human rights principles, ensure equality, and integrate economic, social, and cultural rights into policies. Regional governments need to set budget priorities that support the fulfillment of relevant human rights, with the aim of realizing sustainable and equitable development